Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1111/jdi.13735
|View full text |Cite
|
Sign up to set email alerts
|

Circulating level of fatty acid‐binding protein 4 is an independent predictor of metabolic dysfunction‐associated fatty liver disease in middle‐aged and elderly individuals

Abstract: Aims/Introduction Metabolic dysfunction‐associated fatty liver disease (MAFLD), defined as hepatosteatosis with type 2 diabetes mellitus, overweight/obesity or metabolic dysregulation, has been proposed as a new feature of chronic liver disease. Fatty acid‐binding protein 4 (FABP4) is expressed in adipose tissue, and secreted FABP4 is associated with the development of insulin resistance and atherosclerosis. However, the relationship between MAFLD and FABP4 has not been fully addressed. Materials and Methods A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 59 publications
(98 reference statements)
0
14
0
Order By: Relevance
“…Elevated circulating AFABP level was associated with all the components of metabolic syndrome, including central obesity, insulin resistance, hypertension and atherogenic dyslipidemia, and was an independent predictor of the development of type 2 diabetes 52,53 . A high circulating AFABP level was also shown to be independently associated with ultrasound‐defined NAFLD in type 2 diabetes patients, as well as MAFLD based on the fatty liver index in a recent study of middle‐aged and elderly Japanese individuals 54,55 .…”
Section: Dysfunctional Adipose Tissue As a Common Soil For Nafld In T...mentioning
confidence: 91%
“…Elevated circulating AFABP level was associated with all the components of metabolic syndrome, including central obesity, insulin resistance, hypertension and atherogenic dyslipidemia, and was an independent predictor of the development of type 2 diabetes 52,53 . A high circulating AFABP level was also shown to be independently associated with ultrasound‐defined NAFLD in type 2 diabetes patients, as well as MAFLD based on the fatty liver index in a recent study of middle‐aged and elderly Japanese individuals 54,55 .…”
Section: Dysfunctional Adipose Tissue As a Common Soil For Nafld In T...mentioning
confidence: 91%
“… 11 , 40 The fatty liver index (FLI) is a non-invasive marker calculated using body mass index, waist circumference and levels of γ-glutamyl transferase and triglycerides, and it has a high concordance with the histological criteria for NAFLD. 41 , 42 There have been several studies showing that the FLI is associated with the development of hypertension, 43 diabetes mellitus, 44 chronic kidney disease, 45 heart failure 46 and IHD 47 as well as fibroblast growth factor 21 (FGF21), a hepatokine, 48 and fatty acid binding-protein 4 (FABP4), 49 an atherogenic adipokine with possible therapeutic relevance. 50 , 51 On the contrary, NAFLD fibrosis score (NFS) is widely used to identify individuals with high probability of having advanced liver fibrosis and it is calculated by age, body mass index, presence of impaired fasting glucose or diabetes mellitus, and levels of AST, ALT, platelet count, and albumin.…”
Section: Discussionmentioning
confidence: 99%
“…To the Editor, In a recent issue of the Journal of Diabetes Investigation, Tanaka et al 1 reported valuable findings regarding the relationship of metabolic dysfunction-associated fatty liver disease (MAFLD) and fatty liver index (FLI) with fatty acid binding protein 4 (FABP4) in middle-aged and older adults. This study expanded the overall understanding of the association of hepatosteatosis with altered cytokine production and the independent predictors of MAFLD.…”
mentioning
confidence: 99%